Comprehensive effects of left ventricular assist device speed changes on alveolar gas exchange, sleep ventilatory pattern, and exercise performance - Apostolo, Anna; Paolillo, Stefania; Contini, Mauro; Vignati, Carlo; Tarzia, Vincenzo; Campodonico, Jeness; Mapelli, Massimo; Massetti, Massimo; Bejko, Jonida; Righini, Francesca; Bottio, Tomaso; Bonini, Niccolò; et al. (The Journal of heart and lung transplantation, 2018)
Increasing left ventricular assist device (LVAD) pump speed according to the patient's activity is a fascinating hypothesis. This study analyzed the short-term effects of LVAD speed increase on cardiopulmonary exercise test (CPET) performance, muscle oxygenation (near-infrared spectroscopy), diffusion capacity of the lung for carbon monoxide (Dlco) and nitric oxide (Dlno), and sleep quality. We analyzed CPET, Dlco and Dlno, and sleep in 33 patients supported with the Jarvik 2000 (Jarvik Heart Inc., New York, NY). After a maximal CPET (n = 28), patients underwent 2 maximal CPETs with LVAD speed randomly set at 3 or increased from 3 to 5 during effort (n = 15). Then, at LVAD speed randomly set at 2 or 4, we performed (1) constant workload CPETs assessing O kinetics, cardiac output (CO), and muscle oxygenation (n = 15); (2) resting Dlco and Dlno (n = 18); and (3) nocturnal cardiorespiratory monitoring (n = 29). The progressive pump speed increase raised peak volume of oxygen consumption (12.5 ± 2.5 ml/min/kg vs 11.7 ± 2.8 ml/min/kg at speed 3; p = 0.001). During constant workload, from speed 2 to 4, CO increased (at rest: 3.18 ± 0.76 liters/min vs 3.69 ± 0.75 liters/min, p = 0.015; during exercise: 5.91 ± 1.31 liters/min vs 6.69 ± 0.99 liters/min, p = 0.014), and system efficiency (τ = 65.8 ± 15.1 seconds vs 49.9 ± 14.8 seconds, p = 0.002) and muscle oxygenation improved. At speed 4, Dlco decreased, and obstructive apneas increased despite a significant apnea/hypopnea index and a reduction of central apneas. Short-term LVAD speed increase improves exercise performance, CO, O kinetics, and muscle oxygenation. However, it deteriorates lung diffusion and increases obstructive apneas, likely due to an increase of intrathoracic fluids. Self-adjusting LVAD speed is a fascinating but possibly unsafe option, probably requiring a monitoring of intrathoracic fluids.